Arisan Kurban dalam Persepektif Akuntansi dan Fikih Sosial - Jumaiyah, Jumaiyah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
The purpose of this study was to analyze how the sacrifice of social gathering was conducted by the Javanese people in the perspective of accounting and social fiqh. This study uses a quantitative descriptive method by giving questionnaires to sacrificial social gathering participants. The results of the study show that social sacrifice is an activity with worship advocacy, as the implementation of social fiqh in the world of accounting known as Corporate Social Responsibility (CSR) that must be carried out by each individual, considering that sacrifice is your 'contract worship, recording is done using current cash. Costs incurred for a series of sacrificial social gatherings are not recognized as costs because the committee works for the common interest with the purpose of worship